Crystalline xylitol production from corncob biomass with oral toxicity analysis - Ahuja, Vishal; Dasgupta, Diptarka; Kshirsagar, Siddheshwar; Ghosh, Prasenjit; More, Snehal; Gupta, Piyush; Behera, Babita; Bhaskar, Thallada (Industrial Crops and Products, 2022)
Xylitol, a five-carbon sugar alcohol, has a steady global market and finds application as a natural sugar substitute in various food and confectionery products. Biocatalytic xylitol production, although touted as a greener alternative to conventional chemical catalysis, suffers from certain challenges, the primary being high cost of production. This study demonstrates a process for food-grade xylitol production from corncob biomass with energy reduction through two major process modifications. A non-conventional fermentation strategy was adopted whereby adjusting aeration without agitation, xylitol with high yield (0.86 +/- 0.015 g/g), and productivity (0.74 gL(-1)h(-1)) could be produced by a GRAS Pichia caribbica MTCC 5703 strain. Xylitol was recovered from the broth in the form of crystals using a combination of membrane-based filtration and crystallization. The crystals demonstrated similar to 98 % purity when quantified with H-1 NMR. Oral toxicity analysis of the crystals demonstrated no adverse effect in female Winstar rats (at a loading of 2000 mg/kg body weight of animals). Overall process statistics showed that 0.584 kg of food-grade xylitol crystals could be produced from 3.5 kg of corncob biomass. The two-process modifications during fermentation and xylitol recovery enabled an energy saving of similar to 20.842 kW/kg of crystals, providing tremendous advantages for biorefinery-based large-scale xylitol production from corncob biomass.
Keywords: Biomass; Fermentation; Oral toxicity analysis; Wastewater treatment; xylitol

Process development for detoxification of corncob hydrolysate using activated charcoal for xylitol production - Ahuja, Vishal; Kshirsagar, Siddheshwar; Ghosh, Prasenjit; Sarkar, Bipul; Sutar, Ajit; More, Snehal; Dasgupta, Diptarka (Journal of Environmental Chemical Engineering, 2022)
The work describes process development for detoxification of corncob hydrolysate using activated carbon for microbial xylitol production. Activated carbon was used as an adsorbent to completely remove the major fermentation inhibitors obtained during dilute acid and steam explosion of biomass. A xylitol yield of 0.78 g/g was achieved from the detoxified hydrolysate in a 5 L fermenter by Pichia caribbica. The spent carbon was effectively regenerated and used for three consecutive cycles of operation. The successive regeneration and reuse of carbon could reduce the operational cost by similar to 38% and be used as a reference dataset for process scale-up and cost-effective xylitol production.
Keywords: Activated charcoal; Detoxification; Fermentation; Regeneration; xylitol